The Effectiveness Of Mtrizp Program On Critical Thinking And Problem Solving Skills Among Saudi Arabia's Gifted And Talented Students - Mohammed, Alatawi Atallah (2018)
The purposes of this study were to construct a training program based on the TRIZ program and to measure its effects in enhancing critical thinking and problem solving of talented students. This study used a quasi-experimental method. A quasi experimental approaches were used in the effectiveness of the MTRIZ Program on critical thinking skills and problem solving skills. The study sample in this research consisted of talented seventh, eighth, and ninth graders who attend the Tabuk center in Saudi Arabia. The total sample number was eighty students, whom were divided equally into two groups, control and experimental. The control group received the regular enrichment program that is adopted by the Ministry of Education in Saudi Arabia, whereas the experimental group received the MTRIZ Program. Two instruments were used, watson test, which assessed the students level of critical thinking skills and happner test, which assessed the students level of problem solving skills. These instruments were used to assess the students’ critical thinking skills and problem solving skills pre and post the application of the regular enrichment program or of MTRIZ Program. The data for this research were collected by using both qualitative (interview protocols with participating students) and quantitative (experimental) methodologies. The result of this study showed a significance difference in developing the critical thinking skills and problem solving skills of the talented students between the control and experimental groups (after intervention).